(untitled) (Comprehensive Journal of Science, 2025)
This study aims to trace the verbal pattern Ifta‘ala in all its nominal and verbal forms in Surah Al-Imran, and to analyze it from phonological, morphological, and semantic perspectives. The research adopts a descriptive-analytical methodology that involves extracting all the words occurring in the form Ifta‘ala and its derivatives, followed by a morphological analysis to show how the addition to the basic form (fa‘ala) results in internal modifications that generate semantic shifts by determining their lexical roots and structures. Phonologically, the study investigates sound changes such as substitution, assimilation, and elision; while semantically, it explores how these phonological variations contribute to meaning formation. The study concludes that the Ifta‘ala form expresses a range of meanings including reciprocity, effort, pretension, and affectation, among others. Furthermore, phonological processes such as substitution, assimilation, and elision play a role in lightening the morphological structure while preserving the core meaning .